2009
DOI: 10.1093/wjaf/24.3.144
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Growth of Planted Yellow-Cedar Seedlings and Rooted Cuttings (Stecklings) near Ketchikan, Alaska

Abstract: The survival and growth of yellow-cedar (Chamaecyparis nootkatensis) seedlings and rooted cuttings (stecklings) were monitored for 6 years after planting at three sites near Ketchikan in southeast Alaska to determine whether stecklings could serve as a suitable planting stock. Survival for both seedlings and stecklings was >85% at the three sites. Survival, final diameter, and final height differed by site but not by the use or absence of Vexar as protection from browsing by Sitka black-tailed deer (Odocoil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…While some studies, usually of field plantations, have shown that seedlings grow faster, others have reported growth equal to or slower than that of stecklings. For example, in a nursery trial, yellow-cedar stecklings grew taller and had a greater root collar diameter than seedlings, but both were found to grow to similar sizes in a field comparison trial in British Columbia (Russell 1993); conversely, in Alaskan field experiments, stecklings were reported to be smaller in size than seedlings (Hennon et al 2009). Our findings are consistent with the results obtained frequently for radiata pine (Fielding 1970, Talbert et al 1993, yellow cypress (Karlsson and Russell 1990) and loblolly pine (Frampton et al 2000).…”
Section: Main Effect Of Propagule Typessupporting
confidence: 90%
See 1 more Smart Citation
“…While some studies, usually of field plantations, have shown that seedlings grow faster, others have reported growth equal to or slower than that of stecklings. For example, in a nursery trial, yellow-cedar stecklings grew taller and had a greater root collar diameter than seedlings, but both were found to grow to similar sizes in a field comparison trial in British Columbia (Russell 1993); conversely, in Alaskan field experiments, stecklings were reported to be smaller in size than seedlings (Hennon et al 2009). Our findings are consistent with the results obtained frequently for radiata pine (Fielding 1970, Talbert et al 1993, yellow cypress (Karlsson and Russell 1990) and loblolly pine (Frampton et al 2000).…”
Section: Main Effect Of Propagule Typessupporting
confidence: 90%
“…Stecklings and seedlings had comparable mean RGRs for stem length, leaf, root, stem and total plant biomass, biomass allocation and intrinsic water use efficiency, indicating that these two types of propagule had a similar growth pattern during the early growth phase. Differences between seedlings and stecklings are diverse and differ between tree species, and sometimes within the same species or from nursery to field plantations (Frampton Jr and Foster 1993, Russell 1993, Hennon et al 2009. While some studies, usually of field plantations, have shown that seedlings grow faster, others have reported growth equal to or slower than that of stecklings.…”
Section: Main Effect Of Propagule Typesmentioning
confidence: 99%
“…Drivers of yellow‐cedar decline can be reduced to two factors for risk modelling: soil drainage and snow accumulation. Planting or thinning is often needed to ensure the initial regeneration and competitive ability of C. nootkatensis (Hennon et al. , 2009).…”
Section: Managing Forest Diseases As Climate Changesmentioning
confidence: 99%
“…The performance difference between Yc and Sx could also be due in part to the use of seedlings versus cuttings. Hennon et al (2009) reported larger height and diameter in seedlings of Yc as compared to cuttings.…”
Section: Discussionmentioning
confidence: 92%
“…Planting or thinning is often needed to ensure the initial regeneration and competitive status of yellow-cedar; thus, there is a role for active management (Hennon et al 2009). These activities are directed at higher elevation or on well drained soils where snow or deeper rooting, respectively, protects yellow-cedar roots from lethal cold temperatures.…”
Section: A Proposed Conservation -Management Strategymentioning
confidence: 99%